Dual-Transcriptomic, Microscopic, and Biocontrol Analyses of the Interaction Between the Bioeffector Pythium oligandrum and the Pythium Soft-Rot of Ginger Pathogen Pythium myriotylum - Daly, Paul; Chen, Siqiao; Xue, Taiqiang; Li, Jingjing; Sheikh, Taha Majid Mahmood; Zhang, Qimeng; Wang, Xuehai; Zhang, Jinfeng; Fitzpatrick, David A.; McGowan, Jamie; Shi, Xiujuan; Deng, Sheng; et al. (Frontiers in Microbiology, 2021)
Biological control is a promising approach to suppress diseases caused by Pythium spp. such as Pythium soft rot of ginger caused by P. myriotylum. Unusually for a single genus, it also includes species that can antagonise Pythium plant pathogens, such as Pythium oligandrum. We investigated if a new isolate of P. oligandrum could antagonize P. myriotylum, what changes occurred in gene expression when P. oligandrum (antagonist) and P. myriotylum (host) interacted, and whether P. oligandrum could control soft-rot of ginger caused by P. myriotylum. An isolate of P. oligandrum, GAQ1, recovered from soil could antagonise P. myriotylum in a plate-based confrontation assay whereby P. myriotylum became non-viable. The loss of viability of P. myriotylum coupled with how P. oligandrum hyphae could coil around and penetrate the hyphae of P. myriotylum, indicated a predatory interaction. We investigated the transcriptional responses of P. myriotylum and P. oligandrum using dual-RNAseq at a stage in the confrontation where similar levels of total transcripts were measured from each species. As part of the transcriptional response of P. myriotylum to the presence of P. oligandrum, genes including a subset of putative Kazal-type protease inhibitors were strongly upregulated along with cellulases, elicitin-like proteins and genes involved in the repair of DNA double-strand breaks. In P. oligandrum, proteases, cellulases, and peroxidases featured prominently in the upregulated genes. The upregulation along with constitutive expression of P. oligandrum proteases appeared to be responded to by the upregulation of putative protease inhibitors from P. myriotylum, suggesting a P. myriotylum defensive strategy. Notwithstanding this P. myriotylum defensive strategy, P. oligandrum had a strong disease control effect on soft-rot of ginger caused by P. myriotylum. The newly isolated strain of P. oligandrum is a promising biocontrol agent for suppressing the soft-rot of ginger. The dual-RNAseq approach highlights responses of P. myriotylum that suggests features of a defensive strategy and are perhaps another factor that may contribute to the variable success and durability of biological attempts to control diseases caused by Pythium spp.